P-134 The robustness of Gardner and Schoolcraft (GS) scoring prior vitrification for selecting a single vitrified blastocyst for transfer. (30th June 2022) - Prados Dodd, N; Ruiz, M; Hüttelová, R; Larsson, P; Fernández Sánchez, M; Višnová, H; Mannaerts, B
Abstract: Study question: Do changes in the GS score before vitrification and before transfer of a single vitrified-warmed blastocyst (SVBT) predict the chance of live birth? Summary answer: There was no association between changes in GS score and the chance of live birth after SVBT. What is known already: Morphological scoring of human blastocysts is commonly used for assessing the embryo potential for implantation and live birth. Blastocysts that are vitrified and subsequently warmed are usually observed for re-expansion, which is taken for the decision whether to transfer or if another blastocyst will be warmed. Re-scoring warmed embryos before SVBT may result in a lower, same or higher score and may be applied to select the embryo with the highest quality for transfer. Study design, size, duration: The GS score was evaluated twice namely before vitrification and immediately before SVBT for 374 embryo transfers in 240 women participating in the RAINBOW trial (NCT03564509). Subjects were stimulated with a fixed individualized daily dose of follitropin delta in a long GnRH agonist protocol. Blastocyst transfer was performed on day 5; remaining blastocysts were cryopreserved on day 5/6. Participants/materials, setting, methods: The association between changes in GS score from before vitrification to before SVBT was investigated using a mixed effect logistic regression model with factors for expansion and hatching status, inner cell mass, and trophectoderm (with decrease, no change, and increase as factor levels for each), and assuming that the log-odds of achieving a live birth was normally distributed in the trial population. Main results and the role of chance: A total of 472 embryos were vitrified and scored with the GS grading system before vitrification and before SVBT. Of these 298 (63%) had identical scores before and after vitrification. Changes in expansion and hatching status were seen for 23%, inner cell mass for 21%, and trophectoderm for 21% of embryos. Of the 472 warmed embryos, 32 were discarded and 66 were used for double transfers. The remaining 374 blastocysts were used for single embryo transfers. Of these 374 embryos, 68% had identical GS scores at the two scorings, 12%/6% had increase/decrease in expansion and hatching score, 10%/6% had increase/decrease in inner cell mass grading, and 12%/4% had increase/decrease in trophectoderm grading. There was no statistically significant association between either of these changes and the chance of live birth (expansion and hatching: p = 0.94, inner cell mass: p = 0.71, trophectoderm: p = 0.60). Limitations, reasons for caution: Only 68 (32%) of the 374 blastocysts had different scores before vitrification and before SVBT, indicating the consistency of the score regardless vitrification. Thus, there was only limited power to show an association with chance of live birth. Also, embryos with low quality after thawing were not used for transfer. Wider implications of the findings: Selection of vitrified embryos for transfer can be based on the pre-vitrification score, as the post-vitrification quality correlates well with the pre-vitrification quality and potential changes may not affect the chance of live birth Trial registration number: NCT03564509